Analysis of 79 Hospitalized Severe Epistaxis Patients and Review of Literature - Yazıcı, Demet; Ocar, Gülali; Görgülü, Orhan (ENT Updates, 2022)
Background: In this study, we analyzed the clinical characteristics and outcomes of severe epistaxis patients admitted to our tertiary center and compared our results with the literature. Methods: We retrospectively analyzed clinical records of epistaxis patients admittedto our hospital between January 2018 and December 2019 with respect to their age, gender, duration of hospitalization, anterior/posterior nasal packing, hospitalization month, surgical intervention, bleeding diathesis, comorbid diseases, anticoagulant/antiplatelet drug therapy, blood transfusion, and laboratory values. Results: A total of 79 patients were enrolled in this study, 50 (63.3%) of them were malesand 29 (36.7%) were females. The mean age of all patients was 55.3±17.2. Epistaxis was most common in patients over 70 years of age and the most frequent months for hos-pitalization were January and February. The anterior nasal pack was applied to 74.7% of the patients. The mean hospitalization duration was 3.8±1.8 days (min 2 to max 11)mainly affected by the nasal pack type. The surgical intervention rate was 7.6%, andpatients who needed intervention had lower hemoglobulin values and higher bloodtransfusion rates. The most common comorbid disease was hypertension (54.4%) fol-lowed by cardiac disease (29.1%). The low hemoglobulin value on the day of admissionwas the main factor for blood transfusion and surgical intervention. Conclusions: Despite recent advances in diagnostic modalities of otolaryngology,epistaxis is still one of the most common emergencies with the same basis of treat-ment worldwide. Hypertensive male patients over 50 years of age displayed the major clinical profile of our study group. Non-surgical intervention was the main treatmentmethod, and the duration of hospitalization predominantly depended on nasal packtype. Our study showed physicians should be alert to epistaxis patients with lowhemoglobulin levels as these patients are prone to surgical intervention and blood transfusion.